Psychological and pedagogical conditions for the formation of digital literacy of students of the modern Kazakhstan schools - Balgabayeva, A.E.; Aitzhanova, R.M.; Zhorabekova, D.M.; Tazhibayeva, E.R. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The article discusses the necessity to develop psychological and pedagogical conditions that ensure the success of the process of developing digital literacy among students in the context of digitalization of education. The formation of digital literacy is a comparatively new area of activity that is being applied in many countries of the world and is being actively researched, including Kazakhstan. Digital literacy of students in schools aims at providing effective interaction with digital services, includes the ability to work with any source of information, as well as with all types of information, is expressed in knowledge, skills and abilities that allow students to become active partakers in the socializing Internet environment cyberspace. The authors of the article suggest a classification of psychological and pedagogical conditions that ensure more effective formation of digital literacy of students in the context of digitalization of education in Kazakhstan. However, actual problems and perspectives of the formation of digital literacy is still a scope for further scientific research.
Заманауи Қазақстан мектептері оқушыларының цифрлық сауаттылығын қалыптастырудың психологиялық-педагогикалық шарттары
Психолого-педагогические условия формирования цифровой грамотности учащихся современных казахстанских школ
Keywords: digital competence; digitalization of education; psychological and pedagogical conditions; IT skills